Growth and Production of Corn in Various Planting Distances Systems - Rusnadi Padjung; Muh Farid Bdr; N. Nasaruddin; Ifayanti Ridwan; Muhammad Fuad Anshori; Andi Dwie Mochammad Abduh T; Ahrani Akbar Fachri (Agrotech Journal, 2020)
Corn is one of the most important food commodities consumed by most people in various parts of the country. There is a real interaction between spacing varieties on the observed characters. There are one or more production chatacters that have a significant correlation with production. This research will be carried out at the Experimental Garden of the Bajeng Cereal Research Institute, Bajeng District, Gowa Regency, South Sulawesi, with a coordinate point of 5o18'21.5 "LS, 119o28'38.6" BT. The research was conducted from August to November 2020. This study used a separate plot experimental design. The main plot is a planting system legowo (S) which consists of 3 planting systems, namely the spacing of 75 x 20 cm = 66,667 pop / ha (J1), Legowo (50 + 100) x 20 cm = 66,667 population / ha (J2), and Legowo (50 + 100) x 18 cm = 74,074 population / ha (J3). Meanwhile, the subplots were maize varieties (V), namely NASA 29 (V1), Bisi 2 (V2), and Sinhas 1 (V3). From the research results, it can be concluded that the spacing has no effect on the character of the observation. the variety has a very significant effect on the observed character, except for rod diameter. As for the correlation, the observed characters that had an effect on production were ear length and weight of 1000 seeds